1993
DOI: 10.1128/jb.175.13.4062-4070.1993
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression of ice nuclei in a Pseudomonas syringae strain is induced by nutrient limitation and low temperature

Abstract: Attempts were made to maximize the expression of ice nuclei in Pseudomonas syringae Ti isolated from a tomato leaf. Nutritional starvation for nitrogen, phosphorous, sulfur, or iron but not carbon at 320C, coupled to a shift to 14 to 18'C, led to the rapid induction of type 1 ice nuclei (i.e., ice nuclei active at temperatures warmer than -50C nuclei and the number of bacterial cells in a culture (i.e., ice nucleation frequency) varied with incubation temperature, growth medium composition, culture age, and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
4

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 36 publications
1
66
0
4
Order By: Relevance
“…Another potential disadvantage of retrospectively selecting PM 10 filters for analysis is that IN properties may change during filter storage. Living Pseudomonas syringae, for example, change their IN activity within hours, depending on temperature and nutrient status (Nemecek-Marshall et al, 1993). IN active sites in organisms are proteins (Wolber et al, 1986;Morris et al, 2004).…”
Section: Caveatsmentioning
confidence: 99%
“…Another potential disadvantage of retrospectively selecting PM 10 filters for analysis is that IN properties may change during filter storage. Living Pseudomonas syringae, for example, change their IN activity within hours, depending on temperature and nutrient status (Nemecek-Marshall et al, 1993). IN active sites in organisms are proteins (Wolber et al, 1986;Morris et al, 2004).…”
Section: Caveatsmentioning
confidence: 99%
“…Bacterial abundances are reported as the number of cells per m 3 of air, taking into account the dilution and the volume of air that passed through each filter. For ice nucleation assays, particles were removed from the filters using the same protocol described above, except that the filters were shaken at 4 1C instead of room temperature to minimize warming, which may alter the ice nucleating capabilities of bacterial cells (Nemecek-Marshall et al, 1993). Drop-freeze assays were performed using a protocol described previously (Bowers et al, 2009), which was modified from a protocol described in Vali (1971).…”
Section: Bioaerosol Collectionmentioning
confidence: 99%
“…On the hand, Pooley and Brown (1991) found that large numbers of ice nuclei from P. syringae 1105 were obtained by using Koser citrate broth. Nemecek-Marshall et al (1993) reported that nutrient limitation and low temperature induced high levels of ice nuclei by P. syringae T1. Phosphate starvation and low temperature also induced a high-level expression of ice nuclei in E. herbicola (Fall and Fall, 1998).…”
Section: Discussionmentioning
confidence: 99%